2022
DOI: 10.1155/2022/6437586
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Equity Incentive on Performance Management Based on Balanced Integral Method

Abstract: Improving the equity incentive system has a certain role in promoting the development of the company, but at present, there are relatively few studies on the equity incentive methods of listed companies under the balanced scorecard theory. This paper analyzes the role of equity incentive method of D listed company in enterprise performance management through the balanced scorecard theory and constructs an enterprise financial management evaluation system with qualitative and quantitative characteristics. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Regarding RQ1, the analysis helped us to separate the key directions of performance management such as performance measurement, criteria, relationship, and strategic management. It can be observed that our results are in line with Song (2022), Zhou, et al (2022), and Owais (2021 as they identified that for performance management to be effective, companies' performance needs to be measured by a range of indicators (including financial and non-financial), have clear linkages, and lead to strategic decision-making.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding RQ1, the analysis helped us to separate the key directions of performance management such as performance measurement, criteria, relationship, and strategic management. It can be observed that our results are in line with Song (2022), Zhou, et al (2022), and Owais (2021 as they identified that for performance management to be effective, companies' performance needs to be measured by a range of indicators (including financial and non-financial), have clear linkages, and lead to strategic decision-making.…”
Section: Discussionsupporting
confidence: 85%
“…Performance Management. Over the last two decades, there has been an increasing focus on the research of performance management systems as instruments for effective strategy implementation (Liu, 2022;Song, 2022;Zhou et al, 2022;Owais, 2021). Performance management is defined as "a system that generates performance information through strategic planning and performance management routines and that connects this information to decision venues, where, ideally, the information influences a range of possible decisions" (Moynihan, 2008;p.…”
Section: Theoretical Background: Performance Management and Circular ...mentioning
confidence: 99%